(untitled) (Bangladesh Journal of Animal Science, 2017)
Emerging evidence has shown that municipal garbage waste contains higher amount of heavy metals and increases health and environmental hazards. Little is known, however, about such wastes use as animal food to fate in products level, in dairy cattle roaming freely. To address these, garbage waste as cattle feed, feces and milk samples from roaming dairy cattle were collected from four areas and simultaneously assess heavy metals concentrations. The study areas were Aqua Morolbari (AM; used as control area), Kachijuli Bazar (KB), Machua Bazar (MB), and Mymensingh Medical College (MMC). Emerging evidence has shown that municipal garbage waste contains higher amount of heavy metals and increases health and environmental hazards. Although faeces and milk samples expressed similar trends, feces samples was solely maintained higher chromium concentrations than to garbage waste and milk samples. A significant changes of zinc (Zn) concentrations was observed in collected garbage waste of MB and MMC than to AM and KB. Milk samples showed similar results. In contrast, an increased zinc concentration was found in areas of KB, MB and MMC feces samples as compared to AM. Compared to Aqua Morolbari area, Machua Bazar and Mymensingh Medical College areas garbage contained significant amount of lead (Pb) levels. There was an increase amount of lead presence in feces and milk samples compared to the control zone. A significant amount of cadmium (Cd) was found in KB, MB and MMC compared to AM. Feces samples were responded similarly. In contrast, both MB and MMC showed a higher concentration of cadmium in milk samples than rest of the two sites. From the results, it was clearly revealed that roaming cattle were daily consumed garbage wastes which possessed heavy metals such as Cr, Zn, Pb, and Cd, to a major extent, resulting in introduction of trace elements in the human food chain. Bang. J. Anim. Sci. 2017. 46 (1): 24-28